Novel ABCA4 mutation leads to loss of a conserved C-terminal motif: implications for predicting pathogenicity based on genetic testing. Issue 1 (January 2018) - Wangtiraumnuay, Nutsuchar; Capasso, Jenina; Tsukikawa, Mai; Levin, Alex; Biswas-Fiss, Esther
Purpose: Mutations in the ABCA4 gene result in a broad spectrum of severe retinal degeneration, including Stargardt macular dystrophy, fundus flavimaculatus, autosomal recessive retinitis pigmentosa, and cone-rod dystrophy. In addition to the detection of well-characterized mutations, genetic testing frequently yields novel variants of unknown significance. The purpose of this report is to describe an approach to aid in the assessment of genetic variants of unknown significance. Case report: We report an 11-year-old girl with Stargardt disease harboring novel compound heterozygous deletions of ABCA4 (c.850_857delATTCAAGA and c.6184_6187delGTCT). The pathogenicity of these variants was otherwise unknown. Both deletions introduce premature stop codons and are localized within the open reading frame of ABCA4 . The c.850_857delATTCAAGA occurs early in the gene and leads to a significantly truncated protein of only 317 amino acids. The c.6184_6187delGTCT, is localized to the 3' terminus of the ORF and results in removal of the last 161 out of 2, 273 amino acids of ABCA4, including the VFVNFA motif, which has been shown to be critical in ABCA4 protein function. Homology-based protein modeling of ABCA4 harboring this deletion suggests significant alterations in the protein structure and function. Conclusions: Our analyses allowed us to classify novel variants in ABCA4 as being clearly loss-of-function mutations, and thus pathogenic variants. In cases of variants of unknown significance, appraising the protein structure-function consequences of genetic mutations using in silico tools may help to predict the clinical importance of variants of uncertain pathogenicity.